A methodology for the optimized design of power transformer insulation system. Issue 3 (8th May 2018) - Rodriguez-Ignacio, Hugo; Lopez-Fernandez, Xose M.; Álvarez-Mariño, Casimiro
Abstract : Purpose: The purpose of this paper is to present a methodology based on an optimizer linked with electric finite element method (FEM) for automating the optimized design of power transformer insulation system structures. Design/methodology/approach: The proposed methodology combines two stages to obtain the optimized design of transformer insulation system structures. First, an analytical calculation is carried out with the optimizer to search a candidate solution. Then, the candidate solution is numerically checked in detail to validate its consistency. Otherwise, these two steps are iteratively repeated until the optimizer finds a candidate solution according to the objective function. Findings: The solutions found applying the proposed methodology reduce the inter-electrode distances compared to those insulation designs referenced in the literature for the same value of safety margin. Originality/value: The proposed methodology explores a wide range of insulation system structures in an automated way which is not possible to do with the classical trial-and-error approach based on personal expertise.